Judge's Considerations in Criminalizing the Crime of Plantation Without a Permit in Forest Areas: Decision No. 789/Pid.B/LH/2023/PN.Pdg - Gusti, Mahesa Cakra; Ismansyah (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2025)
Deforestation in Indonesia is a serious issue that has broad impacts on both environmental and legal aspects. One of the main contributing factors is the conversion of forest areas into plantation land without official permits. This act is regulated under Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction and Law Number 6 of 2023 concerning the Job Creation Law. One notable case reflecting this issue is the Timbul Hasibuan case in Nagari Air Bangis, West Pasaman Regency, decided through the Padang District Court Decision Number 789/Pid.B/LH/2023/PN.Pdg, in which the defendant was found guilty of conducting plantation activities within a forest area without a business permit. This study aims to identify the legal considerations of the judges in rendering their decision and to analyze the evidentiary process applied in the case. The research employs a normative juridical method with a descriptive-analytical approach, using both case and statute approaches. Secondary data were used and processed through a legal data editing technique. The results indicate that the panel of judges based their decision on juridical considerations, including the indictment, witness testimonies, evidence, and criminal law provisions, as well as non-juridical considerations such as the defendant’s background and personal condition. However, it was found that relevant facts, such as the defendant’s tax payments and the selective enforcement of law by authorities were not fully considered. Moreover, the ultimum remedium principle in forestry criminal law after the enactment of the Job Creation Law has not been optimally implemented. Therefore, this study emphasizes the need for a more selective, objective, proportional, and equitable enforcement of forestry criminal law to ensure justice for communities living around forest areas.